Pemberdayaan Perempuan Di Desa Gunungsari Melalui Program Penyuluhan Deteksi Kanker Serviks - Amelia, Dessy; Triningsih, Reni Wahyu; Naimah; Aristina, Nur Eva; Rahayu, Sri (DHARMA BAKTI, 2021)
Gunungsari Village, Bumiaji, Batu City is part of the Bumiaji District area with a densely populated area, with a population of 7,526 people. Gunungsari Village is a densely populated area, but the community health status and the participation of women in health programs still need to be improved and empowered. Some of the health problems found in Gunungsari Village are the mothers' lack of knowledge about the incidence of cervical cancer. Cervical cancer is the third leading cause of cancer and the fourth leading cause of death of all types of cancer in women worldwide. In Indonesia, cervical cancer is the cause of cancer and the second cause of death in women due to cancer. In order to optimize cancer prevention and control efforts in Indonesia, there needs to be massive efforts made by all parties, both government and society, in the prevention and control of cancer. Preparing health facilities to provide comprehensive health services, including health promotion, using all media channels by involving community participation. Community service was carried out by playing videos, lectures, question and answer, and pre and post test before and after counseling. The material presented consists of two parts, the first presented was getting to know more about cervical cancer with video playback media and the last presented early detection of cervical cancer through lectures. After being given Health Education about cervical cancer and early detection of cervical cancer with IVA, it was found that the results of community service activities in the leader of health in Gunungsari Village, Bumiaji, Batu City went well and the community was very active in participating in all activities. This is reflected in the enthusiasm to ask questions and discuss and the posttest results show an increase in knowledge.